Factors influencing the utilization of total knee replacement in osteoarthritis knee: A web-based survey of treating doctors - Naman Jain; Yogesh Preet Singh; G C Yathish; Lokesh Veerappa; G Mallinath; Hemant Kalyan; Ishita Shah; Vaibhavi Velangi (Indian Journal of Rheumatology)
Background: India, with its aging population is going to face a major health-care burden due to osteoarthritis (OA) knee in the coming decades. Total knee replacement (TKR) is the most effective way of treating severe OA knee and has a wide variation in its utilization. Objective: The objective of this survey was to gain insight into the factors that influence the treating doctor in considering TKR for a patient and barriers to its utilization. Methods: Rheumatologists, orthopedicians, and physicians were invited to complete a 14-item web-based survey. Results: A total of 217 variable responses were received. The majority were rheumatologists (n = 143; 67.45%). Most felt that TKR was underutilized (n = 134; 62.9%). Functional demands of the patient were the most important patient factor which influenced TKR referral (84%; n = 178). Annual income and availability of health insurance were important socioeconomic factors influencing TKR referral by 105 (50.5%) and 73 (35.1%) respondents, respectively. Financial status (n = 76; 35.8%) was an important patient-related factor influencing TKR decision. High cost was considered the biggest barrier for the underutilization of TKR by 117 (55.5%). Price regulation on knee implants had mixed views, with 94 (46.3%) saying that it had improved access of TKR to a larger population and 90 (44.3%) saying it had not had any impact. Conclusion: High cost and the nonaffordable population remain the biggest barrier to utilization of TKR in OA knee.